2010
DOI: 10.1149/1.3280229
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Dye-Sensitized Solar Cell Through TiCl[sub 4]-Treated TiO[sub 2] Nanotube Arrays

Abstract: Titania nanotube arrays have been fabricated on a fluoride-doped tin oxide substrate by liquid phase deposition using ZnO nanorod arrays as a template and have been applied as the electrode for dye-sensitized solar cells (DSCs). The performance of DSCs based on TiO2 nanotube electrodes can be improved by treating the TiO2 nanotube arrays with titanium tetrachloride (TiCl4) . Both the short-circuit current density and the conversion efficiency increased almost 2 times after the TiCl4 treatment. The TiCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
1
32
1
Order By: Relevance
“…These 1D nanostructures are expected to significantly improve the electron transport properties due to a directional smooth electron mobility (limiting random walk in the wide nanocrystalline network) as well as decreased inter-crystalline contacts, thereby accelerating electron transport and lowering the recombination probability as shown in the schematic diagram of Fig. 5(a), 5(b) [43,44].…”
Section: Tio 2 Nanotubes Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 1D nanostructures are expected to significantly improve the electron transport properties due to a directional smooth electron mobility (limiting random walk in the wide nanocrystalline network) as well as decreased inter-crystalline contacts, thereby accelerating electron transport and lowering the recombination probability as shown in the schematic diagram of Fig. 5(a), 5(b) [43,44].…”
Section: Tio 2 Nanotubes Filmsmentioning
confidence: 99%
“…Nowadays, even more advanced geometries of TiO 2 nanotubes can be prepared by different methods [44,[59][60][61][62][63]. For example, Zheng et al reported the influence of hierarchical structures, constructed via layerby-layer assembly of self-standing titania nanotube arrays and nanoparticles, upon charge recombination and photoelectric performance of front-illuminated DSCs [64].…”
Section: Tio 2 Nanotubes Filmsmentioning
confidence: 99%
“…The resulting desirable morphology would have mesoporous channels and, or nano-columns aligned parallel to each other and in line with the photon and electron current. Such structures provide easier access to film and grain boundaries, allowing for example p-n junction formation under better control and reduce interfacial charge re-combination [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that the electrons that were formed in the transparent anatase TiO2 layerwould be transferred to the FTO glass through the rutile TiO2 nanorods. In addition, the surfacesof the rutile TiO2 nanorods were treated with aqueous TiCl4 solutions that had varying concentrations of TiCl4 for different treatment durations to prevent electron recombination [40].…”
Section: Introductionmentioning
confidence: 99%